Preparation of block copolymers by controlled radical polymerization of acrylamide with functionalized poly(ethylene oxide) as macroinitiator - Bednarek, M.; Biedroń, T.; Kubisa, P. (Polimery, 2022)
Radical polymerization of acrylamide following the atom transfer radical polymerization (ATRP) mechanism (eqn. 1), was studied in aqueous solutions by using ethyl 2-bromopropionate as initiator and a CuBr-amine system as catalyst. With aromatic amine-bipirydyl (BiPy) used as ligand, polymerization was very slow and stopped at very low monomer conversions. With aliphatic amine-pentamethyldiethylenetriamine (PMDETA) used as ligand, polymerization was fast and proceeded until a practically complete conversion of AcAm was attained (Table 1). MALDI TOP analysis of the polymeryzates (Figs. 1-3) showed the polymerization to have been initiated exclusively by the initiator used, but the polymers did not contain a terminal bromine atom, a fact suggestive of side reactions. To prepare block copolymers, poly(ethylene oxide) terminated with ethyl 2-bromopropionate groupings on either end of the chain (MI-PEOX, eqn. 2) was used to initiate radical polymerization of acrylamide. 1H-NMR showed the macroinitiator to have been completely used in the polymerization reaction (Fig. 4). GPC analysis of the copolymerizates (Fig. 5) showed the macroinitiator to have been only partly incorporated into the block copolymer, and the propagation step to have been accompanied by deactivation of the catalyst and by the termination step. Thus, although desired ABA block copolymers were prepared, the control of the copolymerization reaction was incomplete.